Implementation of Counseling by Bhabinkamtibmas via WhatsApp in the Prevention of Theft - Nurlia, Nadya Ayu (Indonesian Journal of Police Studies, 2024)
Research in the background by the high number of vehicle theft in Sumedang Regency, in 2019, there were 113 cases. One factor is the weak level of community awareness. The Binmas Unit has a role to play in preventing prevention, namely approaching the community through counseling, one of which is to convey messages of prevention of fraud through Whatsapp group social media by Bhabinkamtibmas. This study aims to determine the implementation of counseling and the factors that influence the implementation of counseling through Whatsapp which requires a system or mechanism to facilitate the task of Bhabinkamtibmas. Theories and concepts in this study are routine activity theory, function theory and management elements as well as the concept of implementation of counseling with Whatsapp, the concept of Bhabinkamtibmas, the concept of curanmor and Perkap No.21 of 2007. This study uses a qualitative approach with a descriptive type of analysis. Research location in Sumedang Regional Police with a focus on counseling through Whatsapp by Bhabinkamtibmas. Sources of data come from primary, secondary and tertiary data with data collection techniques through interviews, observations, study of data and study of documents and triangulation of data. Data validity through reduction, data presentation, and conclusion / verification. The results found that the implementation of counseling through Whatsapp by Bhabinkamtibmas had not been carried out to the maximum which was analyzed by management function theory and Perkap No.21 of 2007 namely planning, organizing, implementing and controlling as well as judging from the influencing factors analyzed by management element theory including factors The obstacles are the weak managerial of Bhabinkamtibmas personnel and the absence of SOP, while the supporting factors are the budget, supporting facilities and infrastructure as well as the good response from the public regarding the use of Whatsapp. The conclusion is the implementation of counseling by Bhabinkamtibmas through Whatsapp has not been implemented properly.